The tax implications of non-resident sportspersons performing and earning an income in South Africa - Wessels, Jacques (Rhodes University, Faculty of Commerce, Department of Accounting, 2008)
As the number of non-resident sports persons competing in South Africa increases so does the need to tax them more effectively. It was for this reason that the South African legislature decided to insert Part IlIA into the Income Tax Act which regulates the taxation of non-resident sports persons in South Africa. The new tax on foreign sports persons, which came into effect during August 2006, is a withholding tax placing the onus upon the organizer of the event to withhold the tax portion of the payment to the non-resident sportsperson and pay it over to the revenue services. The rate of taxation has been set at 15 percent on all amounts received by or accruing to a foreign sportsperson. The question which the research addressed is whether this new tax will prove to be an effective tax, both from the point of view of its equity and the administration of the tax. In order to determine the impact of the new tax, it was compared to similar taxes implemented in the United Kingdom and Australia and also to other withholding taxes levied in South Africa. The new tax was also measured against a theoretical model for effectiveness, compared to the pre-August 2006 situation and to the taxation of resident sportsmen and women, using hypothetical examples. The major shortcomings of the new withholding tax are the uncertainty with regard to the intention of the legislature on matters such as the taxation of capital income versus revenue income, the question whether payments to support staff are included in the ambit of the new tax, the taxation of the award of assets in lieu of cash payments and the definition of a resident. A further area of concern is that the rate of taxation of 15 percent appears to be too low and creates horizontal inequity between the taxation of resident and non-resident sports persons. The new tax on non-resident sports persons may have its shortcomings but, depending upon the administrative and support structures put in place to deal with it, will be an effective tax. The rate at which the tax is levied could result in a less tax being collected than before but, with the reduced administrative cost of tax collection, the effective/statutory ratio of the tax could well be much higher than it was. This is a new tax in South Africa and certain initial problems are inevitable and will undoubtedly be solved as the administrators gain experience and as the case law governing this tax develops.,KMBT_363
Keywords: South African Revenue Service; Sports -- Taxation -- Law and legislation -- South Africa; Taxation -- Law and legislation -- South Africa; Income tax -- Law and legislation -- South Africa; Income tax -- Foreign income; Income tax -- South Africa -- Foreign income; Withholding tax -- Law and legislation -- South Africa